Alternative Early Childhood Moral Development: Parenting through the Local Wisdom of Lampung People - Ferdian Utama; Leli Fertiliana Dea (Journal of Childhood Development, 2023)
This research aims to explore the role of local wisdom in early childhood moral development through an ethnoparenting approach. Using a case study design and qualitative approach, the research involved in-depth interviews, observation, and documentation to collect data from parents and community leaders. The results showed that Lampung cultural values, such as Piil Pesenggikhi which includes concepts such as Nemui Nyimah, Juluk Adok, Nengah Nyappur, and Sakai Sambayan, serve as a strong foundation in the formation of children's character and morals. Parents play an important role in instilling these values through modeling and habituation in daily life. This research makes a significant contribution to character education in Indonesia by emphasizing the relevance of local wisdom in the context of modern education, while opening up opportunities for further research on the impact of culture on moral development in other communities.